MLN64 contains a domain with homology to the steroidogenic acute regulatory protein (StAR) that stimulates steroidogenesis - Watari, Hidemichi (The National Academy of Sciences of the USA, 1997)
MLN64 is a protein that is highly expressed in certain breast carcinomas. The C terminus of MLN64 shares significant homology with the steroidogenic acute regulatory protein (StAR), which plays a key role in steroid hormone biosynthesis by enhancing the intramitochondrial translocation of cholesterol to the cholesterol side-chain cleavage enzyme. We tested the ability of MLN64 to stimulate steroidogenesis by using COS-1 cells cotransfected with plasmids expressing the human cholesterol side-chain cleavage enzyme system and wild-type and mutant MLN64 proteins. Wild-type MLN64 increased pregnenolone secretion in this system 2-fold. The steroidogenic activity of MLN64 was found to reside in the C terminus of the protein, because constructs from which the C-terminal StAR homology domain was deleted had no steroidogenic activity. In contrast, removal of N-terminal sequences increased MLN64’s steroidogenesis-enhancing activity. MLN64 mRNA was found in many human tissues, including the placenta and brain, which synthesize steroid hormones but do not express StAR. Western blot analysis revealed the presence of lower molecular weight immunoreactive MLN64 species that contain the C-terminal sequences in human tissues. Homologs of both MLN64 and StAR were identified in Caenorhabditis elegans, indicating that the two proteins are ancient. Mutations that inactivate StAR were correlated with amino acid residues that are identical or similar among StAR and MLN64, indicating that conserved motifs are important for steroidogenic activity. We conclude that MLN64 stimulates steroidogenesis by virtue of its homology to StAR.